Whatever happened to online? Multimedia's ugly cousin still shines. - GREGORY, Andrew M. (1994)
Notes that with an increasing number of databases available on CD-ROM, it is tempting to opt for this technology at the expense of online services. Points out the advantages of online systems and the limitations of CD-ROM.